Tailoring traditional Chinese medicine in cancer therapy - Shuiquan Li; Xi Chen; Hui Shi; Ming Yi; Bing Xiong; Tianye Li (Molecular Cancer)
Abstract Cancer remains a formidable global health challenge, necessitating innovative therapeutic approaches to enhance treatment efficacy and reduce adverse effects. The traditional Chinese medicine (TCM), as an embodiment of ancient wisdom, has been validated to regulate the holistic human capacity against both internal and external “evils” in accordance with TCM principles. Therefore, it stands to reason to integrate TCM into current cancer therapy paradigms, such as chemotherapy, immunotherapy, and targeted therapy. This strategy conceptually intends to circumvent the inevitable side effects derived from present treatment, alleviate the discomfort, mollify the detrimental mood and synergize tumoricidal effects of distinct approaches. However, it is still vague whether TCM exert favorable function in cancer treatment. Therefore, it is imperative to retrieve and compile the existing literature on TCM in the realm of cancer, followed by a comprehensive recapitulation and synthesis of its core findings. Recently, with the advancement of contemporary biologic and medical theory and technology, it has become both feasible and imperative to elucidate the molecular signaling mechanisms and cellular biology underlying TCM. Specifically, leveraging TCM pharmaceutic components can not only directly impact tumor biology at the molecular level, but regulate the tumor immune environment through distinct pathways. Additionally, the administration of external TCM treatments such as acupuncture and moxibustion also demonstrates beneficial effects in cancer patients. Through comprehensive analysis, we demonstrated that TCM not only potentially increases the efficacy of conventional cancer treatments, but also significantly mitigates their toxic side effects, thereby prolonging patients’ prognosis and improving their living quality. Furthermore, we have underscored the challenges and prospects associated with the integration of TCM into contemporary oncological practices, placing particular emphasis on the imperative for rigorous clinical trials and molecular investigations to substantiate the efficacy and safety of these combined therapeutic approaches. This synthesis aims to pave the way for a more integrated approach to cancer treatment rooted in both traditional wisdom and cutting-edge science.